ANALISIS PERUBAHAN TUTUPAN LAHAN AREAL KONSESSI TAMBANG PT KALTIM PRIMA COAL - Benteng H Sihombing (Universitas 17 Agustus 1945 Samarinda, 2012)
One way of knowing the land coverage change is through Landsat TM imagery analysis from two periods of running time. It takes at least 2 coverage of the image data to get land cover changes. Mine concession area of PT Kaltim Prima Coal is a product of the area functional transfer of formely the Forest Cultivation Areas (KBK) ex IUPHHK PT Porodisa Ltd. into Other Areas Use (APL) of PT Kaltim Prima Coal mine concession. In the span of two concession, it was necessary to know whether there are changes in land cover during the transition period (the period of 10 years). It can only be known through the analysis of land use change using Landsat TM in 2002 and 1012. The tendency of quality of land cover change that is known through the analysis of these land cover changes and the significance of cover change, are based on information of how the historical of land cover change occurred.